1997
DOI: 10.1152/jappl.1997.82.4.1112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nandrolone decanoate on respiratory and peripheral muscles in male and female rats

Abstract: Bisschop, Anja, G hislaine Gayan-Ramirez, Hélène Rollier, P. N. R ichard D ekhuijzen, René Dom, Vera de Bock, an d Marc D ecram er. Effects of nandrolone decano ate on respiratory and peripheral muscles in male and female rats. J . Appi. Physiol. 82(4): 1112-1118, 1997.-Thirty male and 18 female adult rats received weekly an intramuscular injection of either saline (control; C), 1.5 mg/kg (low-dose; LD) nandrolone decanoate or 7,5 mg/kg (high-dose; HD) nandro lone decanoate during 5 wk. Compared with respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
31
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 30 publications
7
31
2
Order By: Relevance
“…The degree to which type IIx diaphragm fibers hypertrophied after nandrolone administration was almost double that noted for types I and IIa fibers (35). Similarly, Bisschop et al (2) reported selective hypertrophy of type IIx/b fibers of the diaphragm and gastrocnemius muscles of male and female rats given nandrolone decanoate.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The degree to which type IIx diaphragm fibers hypertrophied after nandrolone administration was almost double that noted for types I and IIa fibers (35). Similarly, Bisschop et al (2) reported selective hypertrophy of type IIx/b fibers of the diaphragm and gastrocnemius muscles of male and female rats given nandrolone decanoate.…”
mentioning
confidence: 85%
“…IN RECENT YEARS, it has become clearly evident that anabolic steroids may exert distinct effects on the structure and function of skeletal muscles, including the respiratory muscles, in both animal (2,43,44,48) and human models (1,50). We recently reported that nandrolone administered to adult male hamsters produced significant hypertrophy of all diaphragm muscle fibers and improved isometric and isotonic contractile function (35).…”
mentioning
confidence: 99%
“…Chronic AAS administration did not alter the myosin expression in the plantaris and soleus of female rats (Tsika et al 1987). However, some studies have indicated that this treatment modulated the distribution of ®bre types in the extensor digitorum longus (EDL, a fast-twitch muscle), soleus and red gastrocnemius of female rats (Egginton 1987;Holmang et al 1990), but this eect is not always consistent (Bisschop et al 1997), Thus, there is a need for further inquiry into the eects of decreased and increased levels of AAS on the phenotype of hindlimb muscles in the adult animal. To our knowledge, no study had analysed the eects of AAS (deprivation and administration) on the myosin heavy chain (MHC) expression in both fast-and slow-twitch muscles of the young adult male rat.…”
Section: Introductionmentioning
confidence: 98%
“…Histological examination of the diaphragm has shown gender differences in fiber composition and morphometry (6), but gender differences in phrenic nerve morphology and morphometry have not been examined. Studies that investigated the interaction between hypertension, gender and respiratory control have mainly focused on sleep apnea syndrome (7), and male gender and hypertension have been suggested to be risks for human sleep apnea (8).…”
Section: Introductionmentioning
confidence: 99%